2012
DOI: 10.1096/fj.12-207324
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐mesenchymal transition and fibrosis are mutually exclusive reponses in shear‐activated proximal tubular epithelial cells

Abstract: Renal fibrosis (RF) is thought to be a direct consequence of dedifferentiation of resident epithelial cells via an epithelial-mesenchymal transition (EMT). Increased glomerular flow is a critical initiator of fibrogenesis. Yet, the responses of proximal tubular epithelial cells (PTECs) to fluid flow remain uncharacterized. Here, we investigate the effects of pathological shear stresses on the development of fibrosis in PTECs. Our data reveal that type I collagen accumulation in shear-activated PTECs is accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 47 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…Prior work in our laboratory demonstrated that collagen accumulation in shear-activated PTECs increases with the magnitude of applied shear stress, further corroborating the critical role of hyperfiltration on the progression of renal fibrosis (19). Moreover, ectopic expression of TGF-␤1 evinced distinctly anti-fibrotic effects in shear-stimulated cells (19).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Prior work in our laboratory demonstrated that collagen accumulation in shear-activated PTECs increases with the magnitude of applied shear stress, further corroborating the critical role of hyperfiltration on the progression of renal fibrosis (19). Moreover, ectopic expression of TGF-␤1 evinced distinctly anti-fibrotic effects in shear-stimulated cells (19).…”
supporting
confidence: 66%
“…However, we recently demonstrated that not only are EMT and fibrosis mutually exclusive events in sheared proximal tubular epithelial cells (PTECs), but also that ectopic overexpression of TGF-␤1 in these cells abrogates EMTindependent matrix accumulation via SMAD-dependent mechanisms (19). Consistent with these observations, recent work by Fragiadaki and colleagues (16) identified dynamic dosagedependent effects of TGF-␤1, whereby low concentrations stimulate collagen synthesis but high concentrations suppress it.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, it appears that myofibroblasts may arise from a number of non-fibroblast precursor cells, and these precursors may be of resident or non-resident (bone marrow) origin ( Table 1). The epithelial-mesenchymal transition (EMT) is a possible source of myofibroblasts [28,29], although the extent of its contribution to real-life mechanisms of human fibrotic diseases and animal models of fibrosis remains to be established [30][31][32][33]. Similarly, the endothelial-mesenchymal transition (EndoMT) [34] and the mesothelial-mesenchymal transition (MMT) [35][36][37] may contribute to fibrosis.…”
Section: Collagen-producing Myofibroblasts Originate From Numerous Prmentioning
confidence: 99%
“…The authors conclude that renal fibrosis and EMT could exclude each other. 24 This could be a possible explanation of the fact that in our patients with FSGS tubular aSMA correlated indirectly with interstitial fibrosis, or that it correlated directly with eGFR (in patients with MPGN). It remains, however, difficult to explain why in our patients Vim and aSMA showed different patterns of expression and correlations in TEC.…”
Section: Rastaldi Et Al Have Also Shown In Human Biopsies That Tubularmentioning
confidence: 75%